2017
DOI: 10.1111/cfs.12402
|View full text |Cite
|
Sign up to set email alerts
|

What can agencies do to increase foster carer satisfaction?

Abstract: Stable, long‐term foster care homes are critical to ensuring a safe and nurturing childhood for many children worldwide. Greater foster carer satisfaction is associated with increased carer retention and is therefore critical in securing such stable homes for children. The purpose of this study is to determine which factors associated with foster care agencies contribute to higher levels of foster carer satisfaction. Results from a longitudinal study of 137 foster carers indicate that perceived adequacy of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Even if they were aware of maternal substance use, they may not have been aware of what substances mothers had used. Poor communication between foster carers and social service professionals is a persistent problem repeatedly reported in the literature [ 30 , 31 , 32 ]. In a recent study of 1095 foster carers, less than half ( n = 456, 46%) reported receiving sufficient background information when a child was placed into their care [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if they were aware of maternal substance use, they may not have been aware of what substances mothers had used. Poor communication between foster carers and social service professionals is a persistent problem repeatedly reported in the literature [ 30 , 31 , 32 ]. In a recent study of 1095 foster carers, less than half ( n = 456, 46%) reported receiving sufficient background information when a child was placed into their care [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The very limited notice of a young person arriving, as described by some carers here, is consistent with findings in other localities (Sirriyeh, 2013) and reinforces the need for advance preparation. Carers’ recollections of not having known what to expect the first time an unaccompanied young person moved into placement carry particular weight in the light of previous research, which has indicated that clear expectations before a placement can help to avoid disappointment (Sinclair, Gibbs and Wilson, 2004), improve carers’ sense of preparedness (Geiger, Hayes and Litz, 2014) and enhance their sense of being supported by their fostering agency (Randle, Miller and Dolnicar, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As part of their caregiving role, foster carers are supported by and accountable to foster care agencies (Randle, Miller and Dolnicar, 2017). These are responsible for providing training and facilitating access to professional services, respite and financial support.…”
Section: Introductionmentioning
confidence: 99%